Labour market and social policy development in Poland - Stanislawa Golinowska (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2004)
The article describes (concentrates on the description of) the employment development and social problems related to labour market situation in Poland during the transition period (before the EU accession). It consists of four parts. The first gives an overview of basic tendencies in labour changes and explains periodical development in the labour market situation with negative effects: reduction in employment levels and increase in unemployment scale. We can observe very dynamic structural changes in the general tendencies: from industry to services with limitation of agriculture, from public economy to private one and from low labour productivity to a high one with the phenomenon of jobless growth. The second part of the text presents general tendencies among the most risk groups from the unemployment perspective: disabled people, young and elderly people, women, people living in the countryside and in underdeveloped regions. The relatively bad labour market situation of these risk groups is strongly influenced by their low level of skills and qualifications. In the third part of the paper basic social consequences of the difficult situation on the labour market are being presented: willingness to emigrate, growth of the grey economy and rising poverty and social exclusion. The author points out, that the disadvantages of the current policy afflict first of all the young generation. The fourth and last part of the paper analyses labour market and social policy: as well the national as the EU policy. It depicts weak points of active labour market policy (ALMP) in Poland and high transfers for elderly people threatened by unemployment because of the dynamic restructuring of the economy. Support for the employment priority, necessary to Fight unemplyoment and social exclusion is being seeked for in the European Employment Strategy. Research results presented in the study were collected mainly during the work on the UNDP Report NHDR 2004 'W trosce o prace: ('Caring for a job'), which was prepared under the leadership of the author.
Keywords: 330; Arbeitsmarktentwicklung; osteuropäischer Transformationsprozess; Sozialpolitik - Entwicklung; Arbeitslosigkeitsentwicklung; Arbeitslosenquote; Arbeitsmarktrisiko; Behinderte; ältere Arbeitnehmer; junge Erwachsene; Frauen; strukturschwache Räume; ländlicher Raum; Niedrigqualifizierte; soziale Situation; Massenarbeitslosigkeit - Auswirkungen; Schattenwirtschaft; Armut; soziale Ausgrenzung; Arbeitsmarktpolitik; regionale Disparität; Erwerbsquote; Lohnentwicklung; Sozialleistungen; europäische Integration; Jugendarbeitslosigkeit; Arbeitslosigkeitsbekämpfung; Emigration; Polen